Basic Life Support: A Questionnaire Survey to Assess Proficiency of Radiologists and Radiology Residents in Managing Adult Life Support in Cardiopulmonary Arrest and Acute Anaphylactic Reaction - Tariq Alam; Yasir Jamil Khattak; Muhammad Anwar; Asif Alam Khan (Emergency Medicine International)
The aim of this paper is to assess proficiency of radiologists and radiology residents in managing adult life support in cardiopulmonary arrest and acute anaphylactic reaction.